THE ASSOCIATION BETWEEN SERUM VITAMIN D LEVELS AND LIPID PROFILES AMONG PEOPLE WITH EPILEPSY - Santoso Jaeri; Elisabeth Shanti Regita Putri; Caraka Adhika Rahardjo; Alivia Azka Fadhilah; Arinta Puspita Wati; Lusiana Batubara; Hardian Hardian (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2026)
Background and Purpose: Epilepsy, a neurological condition, is defined by the occurrence of unprovoked seizures on at least two occasions, with a minimum interval of 24 hours separating the initial and subsequent events. Individuals diagnosed with epilepsy frequently exhibit vitamin D deficiency, which influences various metabolic processes, including modifications to lipid profiles. Despite this, the precise relationship between serum vitamin D levels and lipid profiles continues to be a subject of ongoing investigation. This study aimed to examine the correlation between serum vitamin D concentration and lipid profiles. Methods: A cross-sectional study design was employed, encompassing 29 patients with epilepsy who were treated at the outpatient clinic of the Department of Neurology, Diponegoro National Hospital, Semarang. Participants were divided into two groups based on their serum vitamin D levels: the vitamin D deficiency group (n=9) and the vitamin D insufficiency group (n=20). Demographic and clinical information was gathered, vitamin D levels were measured using ELISA, and lipid profiles were assessed using spectrophotometry. A chi-square analysis was conducted to explore the relationship between serum vitamin D levels and lipid profiles in patients with epilepsy. Results: The average vitamin D concentration was 13.45 ± 5.74 ng/mL, with all participants showing deficient vitamin D. Examination of lipid profiles indicated mean values for total cholesterol at 183.76 ± 38.34 mg/dL, LDL cholesterol at 103.55 ± 34.92 mg/dL, HDL cholesterol at 48.72 ± 15.98 mg/dL, and triglycerides at 158.14 ± 104.48 mg/dL. Statistical analysis revealed that LDL levels were significantly elevated in the group with insufficient vitamin D (p = 0.029), while there were no significant differences in triglyceride, total cholesterol, or HDL levels. Statistical analysis revealed that LDL levels were significantly elevated in the group with insufficient vitamin D (p = 0.029), while there were no significant differences in triglyceride, total cholesterol, or HDL levels. Conclusion: There may be a link between low vitamin D levels and adverse LDL cholesterol levels; however, further research is required to confirm this.